BEBENATO Media as a Means of Introducing the Cooperation Character of Elementary School Students - Sakti, Radite Argha Pramudya; Rahmawati, Fitri Puji (Universitas Pendidikan Ganesha, 2023)
This research is motivated by the lack of interest from students to understand the collaborative material provided by the teacher. This study aims to analyze the BEBENATO learning comic media as a medium for teaching and instilling the character of cooperation to elementary school students. The method used in this study is a qualitative approach. The data used are descriptions of the BEBENATO learning comic media and the results of assessments from media experts, material experts, and students. The source of this study is the BEBENATO learning comic medium. Collecting data using interviews, documentation, and the analysis of product validation sheets This study uses a qualitative data analysis process that includes data reduction, data presentation, and drawing conclusions. The results of validation from media experts obtained a percentage of 80% or more, validation results from material experts obtained a percentage of 97.75% or more, and results of validation by students obtained a percentage of 100% or more, with notes such as improvement of background color, connectedness between stories and material, and pictures that don't describe the atmosphere. This medium can be a good tool to introduce and teach the character of cooperation to elementary school students. From the results obtained from the experts, it was stated that BEBENATO media was appropriate to be used to introduce and teach the character of cooperation to elementary school students.